2016
DOI: 10.1002/nag.2525
|View full text |Cite
|
Sign up to set email alerts
|

A fully coupled element‐free Galerkin model for hydro‐mechanical analysis of advancement of fluid‐driven fractures in porous media

Abstract: SUMMARYHydraulic fracturing (HF) of underground formations has widely been used in different fields of engineering. Despite the technological advances in techniques of in situ HF, the industry uses semi-analytical tools to design HF treatment. This is due to the complex interaction among various mechanisms involved in this process, so that for thorough simulations of HF operations a fully coupled numerical model is required.In this study, using element-free Galerkin (EFG) mesh-less method, a new formulation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The reasons for its limited success are mostly related to integration procedures (underlying mesh), data structure, and weight functions for handling fracture propagation in a simple and accurate manner. Recently, Samimi and Pak (2016) have proposed a algorithm based on EFG and an implicit time stepping scheme for the propagation of a hydraulic fracture in a porous material under plane strain conditions. The fracture propagation appears to be performed in an explicit way, using a computation of the stress intensity factor to set a predefined new fracture increment.…”
Section: Element Free Galerkinmentioning
confidence: 99%
“…The reasons for its limited success are mostly related to integration procedures (underlying mesh), data structure, and weight functions for handling fracture propagation in a simple and accurate manner. Recently, Samimi and Pak (2016) have proposed a algorithm based on EFG and an implicit time stepping scheme for the propagation of a hydraulic fracture in a porous material under plane strain conditions. The fracture propagation appears to be performed in an explicit way, using a computation of the stress intensity factor to set a predefined new fracture increment.…”
Section: Element Free Galerkinmentioning
confidence: 99%
“…For conventional numerical techniques, the simulated morphologies of hydraulic fracturing are quite different from the actual phenomenon, in which one of the challenging and vital effects is fluid‐solid coupling, which remains a focus of disagreement regarding the reliability and accuracy of simulated results in hydraulic fracturing. Samimi and Pak developed a fully coupled element‐free Galerkin mesh‐less method considering fluid‐solid coupling for numerical modelling of hydraulic fracture propagation in porous media . A fully coupled finite element and finite volume approach is proposed, which is capable of modelling large‐scale problems involving hydraulically driven fractures in 3D models .…”
Section: Introductionmentioning
confidence: 99%
“…The research showed that the BPM approach can generally capture the brittle failure process of anisotropic rock under uniaxial compression. Samimi and Pak developed an element‐free Galerkin mesh‐less method for the numerical modeling of hydraulic fracture propagation . Settgast et al proposed a fully coupled finite element/finite volume approach, which is capable of modeling large‐scale problems that involve hydraulically driven fractures in 3 dimensions …”
Section: Introductionmentioning
confidence: 99%
“…Samimi and Pak developed an element-free Galerkin mesh-less method for the numerical modeling of hydraulic fracture propagation. 25 Settgast et al proposed a fully coupled finite element/finite volume approach, which is capable of modeling large-scale problems that involve hydraulically driven fractures in 3 dimensions. 26 The overall material response of rock is very complicated, and its anisotropy is governed mainly by micromechanisms such as the formation, growth, and eventual interaction of microcracks.…”
Section: Introductionmentioning
confidence: 99%